2023
DOI: 10.12740/pp/onlinefirst/143982
|View full text |Cite
|
Sign up to set email alerts
|

Common pathomechanism of migraine and depression

Abstract: Migrena i depresja często współwystępują, stanowiąc ważny problem kliniczny. Oba zaburzenia związane są z koniecznością przewlekłego leczenia, a ich wzajemne współwystępowanie sprzyja zjawisku lekooporności. Wpływając na funkcjonowanie pacjentów powodują także liczne konsekwnecje społeczne - oddziałując na jakość życia i realizację celów osobistych osób chorych. W prezentowanej pracy przeglądowej przedstawiono czynniki, które mogą wyjaśniać wspólne patomechanizmy depresji i migreny. Uwzględniono zaburzenia str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Many studies have shown that the inflammatory response is an independent factor leading to MDD after AMI [8,9]. The number of monocytes and neutrophils were increased in the blood of AMI patients.…”
Section: Inflammatory Responsementioning
confidence: 99%
“…Many studies have shown that the inflammatory response is an independent factor leading to MDD after AMI [8,9]. The number of monocytes and neutrophils were increased in the blood of AMI patients.…”
Section: Inflammatory Responsementioning
confidence: 99%
“…It is responsible for meningeal vasodilation and an increase in vascular permeability, favoring the influx of inflammatory cells that would ultimately lead to the activation of microglia, resulting in a neuroinflammatory process. Similarly, in depression, exposure to chronic stress is commonly linked to chronic inflammation, with a pronounced increase in proinflammatory cytokines crossing the blood-brain barrier (BBB), which, in turn, activates the microglia and induces a neuroinflammatory state [390]. Hence, this section aims to recapitulate the main findings about the inflammatory processes shared by migraine and depression.…”
Section: Immune Systemmentioning
confidence: 99%
“…A study revealed that patients with MDD have a two‐fold risk of migraine compared with non‐MDD individuals (Castelnuovo et al., 2016). The coexistence of migraine and depression constitutes the complexity of treatment, and more research on the comorbid mechanisms appears to be worth considering (Wachowska et al., 2023). There are differences in brain volume among patients with MDD and migraine (Ma et al., 2018).…”
Section: Introductionmentioning
confidence: 99%